PERAN ADVERSITY QUOTIENT TERHADAP KESIAPAN KERJA PADA FRESH GRADUATE UNIVERSITAS NEGERI PADANG - Wani Calara Nainggolan, Tysem; Rahmi, Iftita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the role of adversity quotient on work readiness among recent graduates of Padang State University. The background of this study is the high unemployment rate among college graduates, which is caused not only by limited job opportunities but also by low levels of psychological readiness and individual skills. The research method used was quantitative with a cross-sectional design, with a sample of 391 fresh graduates selected using purposive sampling. Data collection was conducted using a Likert scale, then analyzed using simple linear regression. The results of the study indicate that the majority of respondents had an adversity quotient (82.4%) and work readiness (88.2%) in the high category, and that the adversity quotient had a positive and significant effect on work readiness, meaning that individuals with good resilience and the ability to cope with difficulties tend to have higher work readiness.